(untitled) (Ágora Journal, 2024)
The choice of Isabel Lustosa for the title of her work dedicated to the trajectory of Hipólito José da Costa was quite apt. By referring to her subject as "the journalist who imagined Brazil," the author not only presented us with an impeccable narrative about one of the most influential newspaper writers of his time but also prompted us to contemplate how the Luso-Brazilian intelligentsia imagined what Brazil would become. The imaginative dimension is in frank dialogue with Benedict Anderson’s studies on imagined political communities, intrinsically linked to the notion of belonging. After all, Hipólito José da Costa spent more than half of his life outside Brazil, which did not prevent him from writing about and for Brazil. Like the journalist exiled in London, other voices and perspectives also contributed to identifying what Cecília H. de Salles Oliveira called the "tangibility of the nation" – a "Brazilian" identity that was slowly being forged as diverse, although originating from the Portuguese. This dossier aims to bring together studies on different voices of "Brazilian" intelligentsia that, especially in the 19th century, sought to imagine Brazil. These voices, which we understand as plural, include women, Afro-Brazilians, indigenous people, and other historically silenced groups who, despite their political and social marginalization, also thought and forged future alternatives for Brazil. We are, therefore, looking for research that explores debates on national identity, political philosophy, literature, science, and more. We consider both convergences and divergences of thought, highlighting how this diverse intelligentsia helped establish, in a complex and multifaceted manner, Brazilian identity. Therefore, this dossier invites researchers from History, Literature, Social and Political Sciences, as well as other related fields of knowledge, to contribute their analyses on the 19th-century intelligentsia that imagined Brazil.